A Pilot Study of 2-Octyl Cyanoacrylate (Dermabond™) versus Conventional Suture Skin Closures for Caesarean Sections. (December 2014) - Tan, Shu Qi; Malhotra, Rahul; Allen, John Carson; Tan, Thiam Chye
Introduction: 2-octyl cyanoacrylate (Dermabond™, Ethicon, USA) has been available as an alternative skin closure since 1997. There are no reports on keloid formation with 2-octyl cyanoacrylate (2OC) closure for Caesarean section. Our study aims to assess keloid formation after Caesarean sections, as well as the safety and efficacy of 2OC for skin closure in Caesarean sections. Methods: A pilot study of 97 cases of Caesarean section performed by a single surgeon was done — 50 2OC closure versus 47 suture closure. Keloid formation, average operating time, wound infection, wound dehiscence and adverse peri-wound conditions were compared. Proportions across the two series were compared using chi-square/fisher exact test. Average operating time was compared using unpaired t-test. Results: Keloid formation was not statistically significant (2OC 24.0% versus S 14.9%, p=0.382). Mean operating time was similar (2OC 34.1±7.2 minutes versus S 32.7±7.2 minutes, p=0.33). Wound infection rate was similar (2OC 2.0% versus S 2.1%, p=0.939). More women experienced adverse peri-wound conditions with suture closure (2OC 2.0% versus S 6.4%, p=0.303). No woman experienced wound dehiscence. Conclusion: 2-octyl cyanoacrylate has similar efficacy to suture skin closure in terms of keloid formation, operating time, wound infection and adverse peri-wound conditions. It can be a safe alternative for Caesarean section skin closure.